Factors of development skills contribute to the readiness of extension agents during the pandemic outbreak in Malaysia - Khairisham, Khairisyahmie; Mohamed Haris, Nur Bahiah; Shah, Jasmin Arif; Abd Wahab, Jihan (Human Resource Management Academic Research Society, 2023)
Covid-19 was found in Wuhan, China in October 2019 where the disease was expected from wildlife and started to spread in other regions including Malaysia. The first case Covid-19 in Malaysia was found in February 2020 when it was detected by tourists who came back from China. On 18th March 2020, Malaysia’s government announced the Movement Control Order (MCO), in which all of the sectors were interrupted including the agriculture sector. Thus, extension agents need to come out with a solution to help farmers and entrepreneurs during this hard time, to transfer the information, and increase their confidence and knowledge in agriculture during this pandemic. Therefore, this research is aiming to determine the relationship between Program Development Skills; Planning, Implementing, Monitoring and Evaluation towards their readiness to face the pandemic of Covid-19. From the results, monitoring and evaluating skills significantly contributed towards the readiness of extension agents. These two skills explained about 68.7% of the variance in the readiness of the extension agent to face challenges. Therefore, from this study most of the extension agents were ready to prepare or altered their program development skills based on the pandemic outbreak situation. The research would be important as an indicator of the readiness of extension agents and whether they are well prepared for the adjustment during the post-pandemic.